Bantuan Analisis Implementasi Fungsi Manajemen pada Genius Learning Solution (GLS) Academy - Erna Resmiatini; Agustin, Clariza Mahardika; Iftikad, Ismi; Rostyawan, Aldy (Fakultas Ekonomi dan Bisnis Unversitas Islam Raden Rahmat, 2023)
GLS Academy as a computer training and education institution understands that the institution must be able to carry out management functions well. In order to understand whether GLS Academy has carried out management functions as it should, the author through this article provides analytical assistance regarding the implementation of management functions at GLS Academy. The method used is observation for one month and documentation by collecting various kinds of documents needed to support the analysis. As a result, to date GLS Academy has carried out management functions well starting from planning, organizing, directing and implementing, as well as monitoring and controlling. Keywords: Management; Management Function.